REGISTER BAHASA DALAM ACARA ADAT WU’AT WA’I DI MANGGARAI NUSA TENGGARA TIMUR - Silvarius Jasa Halum; Basuki Basuki (Universitas Sarjanawiyata Tamansiswa, 2020)
The objectives of this study are as follows. (1) Describe the form of language registers used in the Wu'at Wa'i program. (2) Describe the meaning of register contained in the traditional Wu'at Wa'i program. (3) Describe the register function contained in the traditional Wu'at Wa'i program. This type of research is a qualitative description. The data of this research are in the form of words and sentences in the Manggarai language which contain registers used in the Wu'at Wa'i program. The research source is the use of the manggarai language in the Wu'at Wa'i program. The data collection was carried out by observing method by using advanced in the form of free listening proficient listening technique, recording technique, and note-taking technique. The data obtained were then analyzed using the matching and split method than using the translational matching technique and the alternate method technique in the form of a technique for direct elements. The method of presenting the results of data analysis in this study is presented informally because it is descriptive. The results of this study are as follows. 1) the form of language registers used in the Wu'at Wa'i program: a) register in the form of words in the Wu'at Wa'i program: (1) register in the form of a single word in the Wu'at Wa'i program. (2) register in the form of a complex word in the Wu'at Wa'i: (a) register in the form of an affixed word. (b) a register in the form of a rephrase. (c) register in the form of compound words. 2) Meaning of Register in Traditional Wu'at Wa'i Events: a) Meaning of lexical and grammatical meanings. b) the meaning of the class. c) denotative meaning and connotative meaning. 3) The register function contained in the traditional Wu'at Wa'i program: a) instrumental function. b) social interaction function. c) poetic function.